ĐÁNH GIÁ HIỆU QUẢ BỘ SINH PHẨM AMPLISENS SHIG/EIEC-SALM-CAMP-F1 PHÁT HIỆN 3 TÁC NHÂN GÂY BỆNH TIÊU CHẢY BẰNG KỸ THUẬT REAL-TIME PCR - Bùi, Thị Thanh Nga; Phạm, Việt Hùng; Lê, Thị Lan Anh; Phạm, Thị Hà Giang; Bùi, Thị Lan Anh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSING THE DIAGNOSTIC EFFICACY OF AMPLISENS SHIG / EIEC-SALM-CAMP-F1 KIT IN DETECTION OF THREE BACTERIA CAUSEING INFECTIOUS DIARRHEA BY REAL-TIME PCR TECHNIQUE Assessing diagnostic efficacy of shig/eiec-salm-camp-f1 (Amplisens) Kit in direction of three bacteria causing cute diarrhea (Campylobacter, Salmonella and Shigella). 96 feces specimens were collected from non-treated pediatric patients with acute diarrhea and 30 controls were collected from normal persons without gastrointestinal disease. The sensitivity and specificity of Amplisen Shig/EIEC-salm-camp-F1 kit (Interlab Servive Company, Russian Federation) were evaluated by using real-time PCR technique. The results showed that Amplisens kit had the high specificity (100%) and high sensitivity (100%). The detection limit was at least 103 CFU/mL. These results were similar to the those of the Sacace kit (standard kit) that has been commercialized in Vietnam. The results also showed that 17.71%, 11.46%, and 7.29 % of the specimens were positive for Campylobacter, Salmonella and Shigella, respectively, in which 1 sample was detected the co-infection of Campylobacter and Salmonella (1.04%). Therefore, the Amplisens kit can be valuable in early diagnosis of acute infectious diarrhea caused by three bacteria including Campylobacter, Shigella, Salmonella in Vietnam.